2014
DOI: 10.1186/1471-2377-14-13
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between cathepsin D C224T polymorphism and Alzheimer’s disease risk: an update meta-analysis

Abstract: BackgroundCathepsin D C224T polymorphism has been reported to associate with AD susceptibility. But the results were inconsistent. This study aimed to assess the relationship between C224T polymorphism and AD risk.MethodsThe relevant studies were identified by searching PubMed, Embase, Web of Science, Google Scholar and Wan fang electronic databases updated on July 2013. The relationship between Cathepsin D C224T polymorphism and AD risk was evaluated by ORs and 95% CIs.ResultsA total of 25 case-control studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Meta-analysis is a valuable tool to identify disease genes [65] leading us to conduct the present study. Our results indicate that the Taq1A homozygote model is associated with schizophrenia susceptibility, as well as the -141C Ins/Del allele frequency and recessive model in all populations studied.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis is a valuable tool to identify disease genes [65] leading us to conduct the present study. Our results indicate that the Taq1A homozygote model is associated with schizophrenia susceptibility, as well as the -141C Ins/Del allele frequency and recessive model in all populations studied.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses on the influence of CTSD mutation rs17571 on AD yielded contrary results ( Schuur et al, 2011 ; Mo et al, 2014 ). Similar discrepancy is also reported for another CTSD mutation (Ala224Val) ( Ntais et al, 2004 ; Paz-Y-Miño et al, 2015 ).…”
Section: Biological Mechanisms Linking Autophagy and Admentioning
confidence: 97%
“…Indeed, several studies reported the association between the rs17571 (C→T) polymorphism and the occurrence of sporadic, late‐onset AD . However, other studies did not confirm this observation, and two recent meta‐analyses again led to contradictory results, one confirming and the other excluding a significant correlation between the expression of A38V cathepsin D and the risk of developing sporadic AD. That said, the studies consistently demonstrate that the expression of the A38V CTSD allele acts in concert with the APOE4 allele in promoting the deposition of Aβ plaques in the brain …”
Section: Introductionmentioning
confidence: 99%